Socialization of Introduction to Campus Life for New Students (PKKMB) Academic Year 2023/2024 Yannas Husada Bangkalan Pharmacy Academy - Teguh Setiawan Wibowo (Jurnal Pengabdian Masyarakat Bestari, 2023)
Higher education is an important stage in the transformation from student to student, namely the change in the phase of human life from adolescence to adulthood who has identity as a complete human being and prepares him to enter the professional world. The method used is presentation of PKKMB material, questions and answers and assistance to important facilities in introducing the campus. The result is community service activities through presentations in PKKMB including presentation of PKKMB material, questions and answers and assistance to campus facilities as an effort to provide assistance to new students to understand the campus environment which is carried out in an orderly manner and gets a positive response. It is hoped that there will be strengthening of networks or partnerships with companies outside campus or alumni who have worked in large companies to provide new students with a broader and more relevant view of the world of work in their chosen major.